Nocturnal sleep is associated with next-day vertical jump performance in collegiate athletes - Hummel, J. W.; Miltenberger, M. M.; Hummer, E. T.; Spaeth, A. M. (The Journal of Strength and Conditioning Research, 2026)
This study examined the relationship between nocturnal sleep and next-day vertical jump performance in NCAA Division I male football athletes. We hypothesized that longer sleep would be associated with better vertical jump performance and explored potential mediators of the relationship, including peak concentric force (N), peak concentric velocity (m·s-1), and countermovement depth (cm). A total of 174 athletes provided 4,049 instances of nocturnal sleep data (measured through photoplethysmography-based smart ring that was worn 5 nights/week) and next-day vertical jump performance. Each week, as part of routine team operations, athletes performed 3 vertical jumps in succession on a force plate and athletic staff calculated maximum and average jump height. A within-subject linear mixed-effects model assessed the relationship between sleep and vertical jump performance, and mediation analysis explored how sleep influenced vertical jump ability. Nocturnal sleep duration averaged 6.2 ± 1.1 hours per night, maximal jump height averaged 41.8 ± 7.8 cm, and average jump height averaged 40.2 ± 7.7 cm. Longer nocturnal sleep duration associated with better next-day vertical jump performance (maximal jump height: SE = 0.062, t = 3.07, 95% confidence interval (CI) [0.07-0.31], p = 0.002; average jump height: SE = 0.063, t = 4.41, 95% CI [0.15-0.40], p < 0.001). Countermovement depth significantly mediated the relationship between sleep and maximal jump performance (ß = -0.18, 95% CI [-0.25 to -0.13], p < 0.001), whereas peak concentric force and peak concentric velocity did not. These findings highlight the importance of prioritizing sufficient nocturnal sleep for optimizing anaerobic performance. Athletic staff should promote sleep hygiene to prevent sleep restriction in student athletes.